BUSINESS VALUATION WITH IRREGULAR CAPITAL EXPENDITURES - MURINA, Hanna (Scientific journal «World of Finance», 2022)
Introduction. The assumption of steady-state annual growth in perpetuity may be justified for cash flows from business operations. However, this assumption is less justified for capital expenditures, which are inherently irregular expenditures on long-term assets. In addition, the irregularity of capital expenditures is a particular characteristic of capital-intensive industries, infrastructure businesses, real estate businesses, and small and medium-sized businesses. To estimate business value in such cases, we propose an improvement that makes the method of discounted cash flows more universal and reliable. The purpose of the article is to derive a formula for normalization of irregular capital expenditures taking into account the impact of inflation and real growth. Results. Business valuation methodology has been complemented with an improvement, which is the formula for normalizing irregular capital expenditures in terminal year. The correctness of the normalization formula is verified by a simulated valuation model of discounted cash flows with a long forecast period. The model indicates that the rules of thumb, such as equating capital expenditures to depreciation, are a source of inaccuracy in business valuations, while the proposed normalization formula is a solution for justified valuation without restrictive and, in many cases, unrealistic assumptions of infinite divisibility and even renewal of fixed assets. Conclusions. The proposed normalization formula increases the reliability of business valuation with irregular capital expenditures and makes the DCF valuation with Gordon growth model more universal.